2016
DOI: 10.1159/000444423
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol Suppression of Parathyroid Hormone Fails to Improve Skeletal Properties in an Animal Model of Chronic Kidney Disease

Abstract: Background: Chronic kidney disease (CKD) leads to complex metabolic changes and an increased risk of fracture. Currently, calcitriol is the standard of care as it effectively suppresses parathyroid hormone (PTH) levels in CKD patients. While calcitriol and its analogs improve BMD and reduce fractures in the general population, the extension of these benefits to patients with advanced kidney disease is unclear. Here, the impact of calcitriol on the skeleton was examined in the setting of reduction in PTH. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Newman et al [ 152 ] used a rat model of progressive CKD (Cy/+), which is characterized by autosomal dominant cystic disease. Starting at 25 weeks of age, Cy/+ male rats were treated with 10 ng/kg BW of calcitriol, intraperitoneally, 3× weekly for 5 weeks.…”
Section: Vitamin K and Vitamin D In Bone Remodeling—in Vivo Studiementioning
confidence: 99%
See 1 more Smart Citation
“…Newman et al [ 152 ] used a rat model of progressive CKD (Cy/+), which is characterized by autosomal dominant cystic disease. Starting at 25 weeks of age, Cy/+ male rats were treated with 10 ng/kg BW of calcitriol, intraperitoneally, 3× weekly for 5 weeks.…”
Section: Vitamin K and Vitamin D In Bone Remodeling—in Vivo Studiementioning
confidence: 99%
“…Summarizing, the recently performed studies showed that the treatment of CKD animals with 1,25D may not improve bone quality [ 152 ], or even can be associated with mineralization defects [ 153 , 154 ]. These observations are consistent with the results of studies performed on non-CKD animals [ 155 , 156 , 157 ], which reported that treatment with calcitriol led to growth plate defects, an accumulation of osteoid and prolongation of mineralization lag time, reduction of cortical thickness, and suppression of bone matrix mineralization.…”
Section: Vitamin K and Vitamin D In Bone Remodeling—in Vivo Studiementioning
confidence: 99%
“…Structural mechanical properties of the left femur were determined by four-point bending as previously described [35]. The anterior surface was placed on two lower supports located ±9 mm from the mid-diaphysis (18 mm span length) with an upper span length of 6 mm.…”
Section: Whole Bone Mechanicsmentioning
confidence: 99%
“…Serum calcium, phosphorus, albumin, creatinine, alkaline phosphatase, parathyroid hormone, blood sugar, vitamin D, hemoglobin, ferritin and ESR were measured in each patient [28][29][30][31].…”
Section: Renal Osteodystrophy In End Stage Renal Disease Patients In mentioning
confidence: 99%